(untitled) (Revista NUPEART, 2025)
This article, situated in the field of Theater Pedagogy, seeks to encourage its readers to consider possibilities for teaching theater based on the methodological traces left by its authors during practices conducted with classes in the Arts curriculum component within the context of Professional and Technological Education offered by IFRN and IFTO. Dialogues with the works of Araújo (2005) and Roubine (1982) enhance our thinking about staging. Regarding play, we have opted for the written works of Boal (2008), Koudela (2001), and Spolin (2008), while Gagnebin (2002) and Freire (2000) help us to consider the methodological paths that allowed us to bring play into the classroom scene. At the end of this writing, we affirm that it is possible to follow the presented methodological traces for experimentation, both in institutions that have EPT as a pedagogical focus and in others that aim to educate students holistically through the teaching of Theater. Theater Pedagogy. Staging. Play. EPT. Education.